Is there a Rationale for Autologous Breast Reconstruction in Older Patients? A Retrospective Single Center Analysis of Quality of life, Complications and Comorbidities after DIEP or ms-TRAM Flap Using the BREAST-Q - Ludolph, Ingo; Horch, Raymund E.; Harlander, Marina; Arkudas, Andreas; Bach, Alexander D.; Kneser, Ulrich; Schmitz, Marweh; Taeger, Christian; Beier, Justus (BREAST J, 2015)
Autologous breast reconstruction with the deep inferior epigastric perforator (DIEP) or muscle-sparing transverse rectus abdominis myocutaneous (ms-TRAM) flap is a common method in the majority of patients after mastectomy. Because of an increased perioperative risk profile the benefit in older patients is questionable. To assess the postoperative quality of life and peri- and post-operative complications of older compared to younger patients is the aim of this retrospective study. In a retrospective analysis 39 older (i.e. >60 years) and 140 younger patients (i.e. <60 years) with autologous breast reconstruction in the Department of Plastic Surgery at the University Hospital of Erlangen-Nuernberg were surveyed at least 6 month postoperative using the BREAST-Q questionnaire. Correlations were generated between comorbidities and complications. Significant differences were observed regarding hospitalization, pre-existing diseases and the choice of DIEP versus ms-TRAM flaps. Parameters such as major and minor complications, bulging or hernia and risk factors (e.g. smoking or obesity) showed no significant differences. The results of the questionnaire parameters showed no significant difference between both groups, revealing high satisfaction with the aesthetic result and an improvement in quality of life independent of age. Autologous breast reconstruction after mastectomy generates a gain in quality of life and shows a good to excellent overall satisfaction in older as well as younger patients. Despite a longer hospitalization and a different risk profile there were no significant differences regarding minor and major complications in the postoperative course. Hence autologous breast reconstruction for older patients is justified and should be taken into consideration.
EVALuna2:15594